On the polynomiality of separately constant functions - Kosovan, V.M.; Maslyuchenko, V.K. (Carpathian Mathematical Publications, 2014)
We establish necessary conditions and sufficient conditions on a set ER^2 under which every separately constant function f:E→ R is polynomial and there exist a separately constant function f_0:E → R which is not constant.